Analysis of Acehnese Historical and Cultural Content on YouTube Based on Islamic Marketing Ethics - Syahrizal, Teuku Muhammad; Najla; Muftahuddin; Meutia Dwi Novita Sari; Nabilah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The development of digital media has transformed patterns of representation and consumption of history and culture through video-based platforms such as YouTube. This study analyzes the production practices of Acehnese historical and cultural content on the Nata the Kongkow YouTube channel by employing Islamic marketing ethics as the primary evaluative framework. Using a qualitative approach with a case study design, the research draws on content analysis and interviews as a means of confirming analytical findings. The results indicate that content production involves ongoing negotiation between educational objectives, limitations of historical sources, and audience engagement demands. From the perspective of Islamic marketing ethics, content production practices have generally fulfilled the principles of sidq, amanah, bayān, and orientation toward public welfare, although the degree of fulfillment varies according to content objectives and available source constraints. These findings demonstrate that Islamic marketing ethics can function as a reflective framework for assessing digital historical and cultural content practices and provide practical implications for content creators and cultural institutions. Abstrak Perkembangan media digital telah mengubah pola representasi dan konsumsi sejarah serta budaya melalui platform berbasis video seperti YouTube. Penelitian ini menganalisis praktik produksi konten sejarah dan budaya Aceh pada kanal YouTube Nata the Kongkow dengan menggunakan etika marketing syariah sebagai kerangka evaluatif utama. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus melalui analisis konten dan wawancara sebagai sarana konfirmasi temuan. Hasil penelitian menunjukkan bahwa produksi konten berlangsung dalam negosiasi antara tujuan edukatif, keterbatasan sumber historis, dan tuntutan keterlibatan audiens. Dari perspektif etika marketing syariah, praktik produksi konten secara umum telah memenuhi prinsip sidq, amanah, bayān, dan orientasi kemaslahatan, meskipun tingkat pemenuhannya bervariasi sesuai dengan tujuan konten dan keterbatasan sumber yang tersedia. Temuan ini menegaskan bahwa etika marketing syariah dapat berfungsi sebagai kerangka reflektif dalam menilai praktik konten digital sejarah dan budaya serta memberikan implikasi praktis bagi konten kreator dan institusi budaya.